Secondary battery and device including said battery

By designing a multi-layer polymer coating on the separator of the lithium-ion battery and adjusting the distance between the positive and negative electrodes, the problems of insufficient battery charge and discharge characteristics and electrolyte delivery obstacles under low temperature conditions are solved, and better battery performance and energy density are achieved.

JP2025511106AActive Publication Date: 2025-04-15NINGDE AMPEREX TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024557884
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-04-15
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

Under low temperature conditions, the actual charging and discharging characteristics of existing lithium-ion batteries are much smaller than the design value, and the expansion of the negative electrode causes electrolyte delivery obstacles, affecting battery performance.

Method used

A secondary battery is designed, and the separator between the positive and negative electrodes comprises a matrix with different surface coatings, the first coating consists of a specific polymer, the second coating consists of another polymer, and by adjusting the distance between the positive and negative electrodes, the electrolyte is ensured in the passage space of curvature and straight portions.

Benefits of technology

By optimizing the separator structure, the impact of negative electrode expansion on electrolyte delivery is alleviated, the charge and discharge characteristics and energy density of the battery under low temperature conditions are improved, and the risk of increasing battery thickness is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511106000001_ABST
    Figure 2025511106000001_ABST
Patent Text Reader

Abstract

The present invention relates to a secondary battery, the secondary battery including a positive electrode, a negative electrode, and a separator provided between the positive electrode and the negative electrode, the positive electrode, the separator, and the negative electrode being laminated and wound in order to form a wound structure including a curved portion and a flat portion, the separator including a base material having a first surface and a second surface facing the first surface, a first coating layer being provided on the first surface of the base material, a second coating layer being provided on the second surface of the base material, in the curved portion of the wound structure, when the distance between the adjacent negative electrode and positive electrode is d1, and in the flat portion of the wound structure, when the distance between the adjacent negative electrode and positive electrode is d2, 1 < d1 / d2 < 10 is satisfied. The d1 and d2 adopt the same unit.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of storage, in particular to secondary batteries and devices containing such batteries. [Background technology]

[0002] With the popularity of electronic products such as laptops, mobile phones, portable game consoles, and tablet PCs, people are making stricter demands on electrochemical devices (e.g., batteries). Among many batteries, lithium-ion batteries have the characteristics of high energy density, high operating voltage, low self-discharge rate, small volume, and light weight, and are widely used in various fields such as electrical energy storage, portable electronic products, and electric vehicles. Summary of the Invention

[0003] As the application of lithium-ion batteries in consumer devices and other fields develops rapidly, the requirements for the charge-discharge cycle characteristics and energy density of lithium-ion batteries are also becoming higher. However, under low temperature conditions, the actual charge-discharge characteristics of lithium-ion batteries are far smaller than the designed values, which restricts the further application of lithium-ion batteries.

[0004] At present, most lithium-ion batteries manufactured using conventional battery technology have a negative electrode that continues to expand during cycling, which causes the space between the positive and negative electrodes to be compressed, making the space for electrolyte transport smaller and smaller, ultimately resulting in electrolyte transport failure. In particular, in the curved part, the electrolyte transport failure in the curved part is most serious because stress is concentrated here. Especially during low-temperature cycles, it is easy to cause electrolyte supply to be insufficient in the curved part, which causes the electrolyte bridge to break, resulting in lithium absorption deficiency and lithium precipitation in the curved part, thereby affecting the performance of the battery.

[0005] To improve the above-mentioned defects, the common practice in this field is to increase the gap between the positive electrode and the negative electrode at the initial stage of the battery, and ensure space for the expansion of the negative electrode, so as to relieve the transport obstacle of the electrolyte. However, the drawback of this method is that both the gap in the curved part of the battery and the gap in the flat part of the battery increase, the thickness of the battery increases, resulting in a loss of the volume energy density of the battery.

[0006] To solve the above problems and other problems existing in this field, as one aspect, the present invention provides a secondary battery. The secondary battery includes a positive electrode, a negative electrode, and a separator provided between the positive electrode and the negative electrode. The positive electrode, the separator, and the negative electrode are stacked and wound in sequence to form a wound structure including a curved part and a flat part. The separator includes a base material, and the base material has a first surface and a second surface opposite to the first surface. A first coating layer is provided on the first surface, the first coating layer includes a first polymer, a second coating layer is provided on the second surface. When the distance between the adjacent negative electrode and positive electrode in the curved part is d1, and the distance between the adjacent negative electrode and positive electrode in the flat part is d2, d1 and d2 satisfy 1 < d1 / d2 < 10. The d1 and d2 adopt the same unit.

[0007] In some embodiments, in a region of 250μm×200μm on the surface of the first coating layer, the number of particles of the first polymer with a maximum length between 10μm and 30μm is 10 to 30.

[0008] In some embodiments, the first polymer includes a homopolymer formed from any one of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride, or the first polymer includes a copolymer formed from at least two monomers selected from the group consisting of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride.

[0009] In some embodiments, the first polymer has a softening point of 90°C to 150°C.

[0010] In some embodiments, the first polymer has a Dv50 of 3 μm to 16 μm.

[0011] In some embodiments, the ratio of the orthogonal projected area of ​​the first coating layer on the first surface to the area of ​​the first surface is between 5% and 60%.

[0012] In some embodiments, the coating areal density W1 of the first coating layer is 0.4 g / m 2 ~2g / m 2 It is.

[0013] In some embodiments, the second coating layer comprises a second polymer, wherein the second polymer has a Dv50 of 0.2 μm to 8 μm.

[0014] In some embodiments, the second polymer comprises a homopolymer formed from any one of the monomers ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene, or the second polymer comprises a copolymer formed from at least two monomers selected from the group consisting of ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene.

[0015] In some embodiments, the coating surface density W2 of the second coating layer is 0.1 g / m 2 ~1g / m 2 It is.

[0016] In some embodiments, the adhesive strength between the first coating layer and the positive electrode is 4 N / m to 20 N / m, or the adhesive strength between the second coating layer and the negative electrode is 5 N / m to 20 N / m.

[0017] In some embodiments, the adhesive strength between the first coating layer and the negative electrode is 3 N / m to 15 N / m, and the adhesive strength between the second coating layer and the positive electrode is 5 N / m to 20 N / m.

[0018] In some embodiments, when the number of wound layers of the positive electrode and the negative electrode is N, N satisfies N≧4.

[0019] In some embodiments, the first coating layer is provided on the curved portion.

[0020] In some embodiments, the first coating layer and / or the second coating layer includes inorganic particles. The inorganic particles in the first coating layer or the second coating layer account for 40% to 90% of the total weight of the coating layers. In some other embodiments, the separator further includes a heat-resistant layer. The heat-resistant layer may be provided between the substrate and the first coating layer or between the substrate and the second coating layer. The heat-resistant layer includes inorganic particles.

[0021] In another aspect, the present invention provides an electrochemical device comprising a secondary battery according to any of the above examples.

[0022] In yet another aspect, the present invention provides an electronic device including the secondary battery according to any of the above embodiments. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a structural schematic diagram of a battery according to some embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will be described in detail below. It should be understood that the terms used in the specification and the appended claims should not be limited to the general meaning and dictionary meaning, but should be interpreted based on the meaning and concept corresponding to the technical aspects of the present application based on the principle that allows the inventor to properly define the terms and perform the best interpretation. Therefore, the description shown in the embodiment described in the specification is merely a specific example for the purpose of explanation, and is not intended to show all the technical aspects of the present application. It should also be understood that multiple optional equivalents and variants can be completed when presenting the present invention.

[0025] As used herein, the terms "approximately," "roughly," "substantially," and "about" are used to describe and illustrate small variations. When used in conjunction with an event or situation, the term can refer to instances in which the event or situation occurred exactly, and instances in which the event or situation occurred very similarly. For example, when used in conjunction with a numerical value, the term can refer to a variation range of ±10% or less of the numerical value, such as ±5% or less, ±4% or less, ±3% or less, ±2% or less, ±1% or less, ±0.5% or less, ±0.1% or less, or ±0.05% or less. For example, two numerical values ​​are considered to be "approximately" the same if the difference between the two numerical values ​​is ±10% or less of the average value of the numerical values ​​(e.g., ±5% or less, ±4% or less, ±3% or less, ±2% or less, ±1% or less, ±0.5% or less, ±0.1% or less, or ±0.05% or less).

[0026] In specific embodiments and in the claims, a list of items connected by the terms "one of," "one of," "one of," or other similar terms means any of the listed items. For example, if item A and item B are listed, the short phrase "one of A and B" means only A or only B. In other examples, if items A, B, and C are listed, the short phrase "one of A, B, and C" means only A, only B, or only C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0027] In specific embodiments and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms means any combination of the listed items. For example, if item A and item B are listed, the short phrase "at least one of A and B" means A only, B only, or A and B. In other examples, if items A, B, and C are listed, the short phrase "at least one of A, B, and C" means A only, or B only, or C only, or A and B (excluding C), or A and C (excluding B), or B and C (excluding A), or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0028] It should be noted that amounts, ratios, and other numerical values ​​may be presented in a range format herein. Such range formats are used for convenience and brevity and should be interpreted flexibly, and such ranges include not only the numerical values ​​expressly specified as range limits, but also all individual numerical values ​​or subranges contained within the range, as if each numerical value and subrange were expressly specified.

[0029] 1. Secondary battery: The present invention provides a secondary battery. The secondary battery includes a positive electrode, a negative electrode, and a separator provided between the positive electrode and the negative electrode. The positive electrode, the separator, and the negative electrode are laminated and wound in order to form a wound structure including a curved portion and a flat portion. The separator includes a base material having a first surface and a second surface facing the first surface. A first coating layer is provided on the first surface, and the first coating layer includes a first polymer. A second coating layer is provided on the second surface. In the curved portion, when the distance between the adjacent negative electrode and positive electrode is d1, and in the flat portion, when the distance between the adjacent negative electrode and positive electrode is d2, 1 < d1 / d2 < 10 is satisfied. d1 and d2 adopt the same unit. The flat portion in the wound structure may be, for example, the basically parallel upper or lower part in FIG. 1, and the curved portion may be, for example, the part connecting the two flat portions of the upper and lower parts in FIG. 1 (FIG. 1 shows only the left part and omits the right part). Here, "upper", "lower", "left" and "right" are the relative positions of each part of the battery in FIG. 1, and have different orientations depending on the arrangement position and observation angle of the battery.

[0030] In some embodiments, d1 / d2 is in the range of about 1.05, about 1.5, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or a range consisting of any two of the above values.

[0031] As can be seen from the research of the present invention, a separator is provided between the positive electrode and the negative electrode, and the separator is designed to include a base material, a first coating layer and a second coating layer respectively located on two opposing surfaces of the base material. The first coating layer contains a first polymer, and the distance d1 between the adjacent negative electrode and positive electrode at the curved portion of the battery and the distance d2 between the adjacent negative electrode and positive electrode at the flat portion of the battery satisfy 1 < d1 / d2 < 10 (see Figure 1). By having the configuration as described above, it is possible to provide a space for alleviating the expansion of the negative electrode during the cycling of the battery, thereby avoiding local loss of the electrolyte caused by the electrolyte being compressed and discharged. It is possible to avoid the situation where the gap of the battery is too large and there is not enough amount of electrolyte to fill the gap, resulting in local loss of the electrolyte, and it is possible to ensure that the thickness of the main body portion (i.e., the flat portion) of the battery does not increase significantly. Furthermore, the hardness of the battery can be guaranteed and the adhesion between the separator and the positive and negative electrodes can be improved. Finally, the rate characteristics and cycle characteristics of the battery can be enhanced, and losses such as the loss of the volume energy density of the battery can be reduced.

[0032] In some embodiments, in a region of 250 μm × 200 μm on the surface of the first coating layer, the number of particles of the first polymer with a maximum length between 10 μm and 30 μm is 10 to 30. In some embodiments, the number of particles of the first polymer under the above conditions is about 10, about 15, about 20, about 25, or about 30, or within a range consisting of any two of these numerical values. As can be seen from the research of the present invention, by controlling the number of particles of the first polymer within this range, a better thickness of the curved portion of the battery can be obtained. The larger the number of particles, the larger the corresponding d1.

[0033] In some embodiments, the first polymer includes a homopolymer formed from any one of the monomers of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride, or the first polymer includes a copolymer formed from at least two monomers selected from the group consisting of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride. In some embodiments, the first polymer is polyvinylidene fluoride. In some embodiments, the first polymer is a copolymer of polyvinylidene fluoride and hexafluoropropylene or vinyl chloride, for example, a copolymer of 95 wt% polyvinylidene fluoride and 5 wt% hexafluoropropylene or 5 wt% vinyl chloride. A homopolymer formed from any of the monomers or a copolymer formed from at least two of the monomers can realize the technical solution of the present application and obtain ideal battery characteristics. However, as can be seen from further research of the present invention, on the one hand, when the conventional aqueous polyvinylidene fluoride (PVDF) is used as the first polymer to form the first coating layer of the separator, its large particle size can ensure space for the expansion of the negative electrode, but due to the high softening point of the material, the adhesive strength at the interface is low, and the loss of energy density of the battery is large. In addition, the hardness of the battery is low, which makes it easy to deform during assembly and the winding structure is easy to shift, which causes safety risks. In addition, the hardness is low, and during the charging and discharging process of the battery, the interface between the positive electrode and the negative electrode is not flat due to the disordered expansion of the negative electrode, which causes localized lithium precipitation, which affects the battery characteristics. On the other hand, when the non-aqueous PVDF is used as the first polymer to form the first coating layer of the separator, after being hot pressed, the gap at the interface is very small, which is easy to hinder the transport of the electrolyte, and both the body and corners of the battery are prone to electrolyte deficiency, which causes lithium absorption deficiency, and further causes lithium precipitation. However, adding at least one of hexafluoropropylene, ethylene, propylene, vinyl chloride or propylene chloride to PVDF as the first coating layer can provide an ideal space for the expansion of the negative electrode and ensure the adhesion between the separator and the positive and negative electrodes.

[0034] In some embodiments, the softening point of the first polymer is 90°C to 150°C. In some embodiments, the softening point of the first polymer is about 95°C, about 100°C, about 105°C, about 110°C, about 115°C, about 120°C, about 125°C, about 130°C, about 135°C, about 140°C, or about 145°C, or within a range consisting of any two of these values. If the softening point of the first polymer is too low, the phenomenon of blocking the pores of the separator is likely to occur, affecting the transportation of lithium ions and ultimately affecting the electrical characteristics of the battery, and if the softening point of the first polymer is too high, the adhesive force between the separator and the electrode piece is reduced, causing the active material to fall off during cycling, and ultimately affecting the electrical characteristics of the battery. By controlling the softening point of the first polymer within the above range, ideal electrical characteristics can be obtained.

[0035] In some embodiments, the Dv50 of the first polymer is 3 μm to 16 μm. In some embodiments, the Dv50 of the first polymer is about 4 μm, about 5 μm, about 6 μm, about 7 μm, about 8 μm, about 9 μm, about 10 μm, about 11 μm, about 12 μm, about 13 μm, about 14 μm, or about 15 μm, or is within a range consisting of any two of these values. The larger the Dv50 of the first polymer, the easier it is to create a desired gap (i.e., the d1) in the curved part of the battery, but if the Dv50 is too large, the volumetric energy density of the battery decreases. By controlling the Dv50 of the first polymer within the above range, it is possible to reduce the loss of volumetric energy density while ensuring space for the expansion of the negative electrode.

[0036] In some embodiments, the first coating layer further comprises a first auxiliary binder. The mass ratio of the first polymer to the first auxiliary binder is 2.5 to 18. In some embodiments, the mass ratio of the first polymer to the first auxiliary binder is 3, 5, 7, 9, 11, 13, 15, or 17, or within a range consisting of any two of these values. Without being limited to any theory, if the mass ratio of the first polymer to the first auxiliary binder is too low (e.g., less than 2.5), the content of the first polymer decreases, and the gaps caused by the particulate first polymer decrease, affecting the transport of the electrolyte between the interfaces of the first coating layer, and at the same time affecting the adhesive force between the first coating layer and the electrode piece. If the mass ratio of the first polymer to the first auxiliary binder is too high (e.g., more than 18), the internal cohesion of the first coating layer decreases, and the adhesive performance of the first polymer decreases with the decrease in the internal cohesion of the first coating layer. By controlling the mass ratio of the first polymer to the first auxiliary binder within the above range, excellent adhesive strength can be provided between the first coating layer and the electrode piece.

[0037] The first auxiliary binder is not particularly limited as long as it satisfies the requirements of the present invention, and may include, for example, at least one of polymethyl methacrylate, polyacrylonitrile, ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene.

[0038] In some embodiments, the mass percentage of the first polymer is 85% to 95% and the mass percentage of the first auxiliary binder is 5% to 15% relative to the total mass of the first coating layer. By controlling the contents of the first polymer and the first auxiliary binder within the above ranges, a first polymer having excellent adhesive performance can be obtained, and high adhesive strength can be provided between the first coating layer and the positive electrode, thereby improving the performance of the lithium ion battery at low temperatures.

[0039] In some embodiments, the first coating layer further comprises a first wetting agent. The first wetting agent is not particularly limited and may be any agent that satisfies the requirements of the present invention, for example, polyoxyethylene ether. The mass percentage of the first wetting agent is 0.1% to 1% with respect to the total mass of the first coating layer.

[0040] In some embodiments, the orthogonal projection area of ​​the first coating layer on the first surface is between 5% and 60% of the area of ​​the first surface, and in some embodiments, the percentage is about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, or about 55%, or any range consisting of any two of these values.

[0041] In some embodiments, the coating areal density W1 of the first coating layer is 0.4 g / m 2 ~2g / m 2 In some embodiments, the coating areal density W1 of the first coating layer is about 0.5 g / m 2 , about 0.6g / m 2 , about 0.7g / m 2 , about 0.8g / m 2 , about 0.9g / m 2 , about 1.0g / m 2 , about 1.1g / m 2 , about 1.2g / m 2 , about 1.3g / m 2 , about 1.4g / m 2 , about 1.5g / m 2 , about 1.6g / m 2 , about 1.7g / m 2 , about 1.8g / m 2 , or about 1.9 g / m 2 or within a range consisting of any two of these values. The smaller the coating surface density W1 of the first coating layer, the smaller the thickness of the curved portion of the battery. By controlling the coating surface density W1 of the first coating layer within the above range, better electrical characteristics can be achieved.

[0042] In some embodiments, the second coating layer comprises a second polymer.

[0043] In some embodiments, the Dv50 of the second polymer is between 0.2 μm and 8 μm. In some embodiments, the Dv50 of the second polymer is about 0.5 μm, about 1.0 μm, about 1.5 μm, about 2.0 μm, about 2.5 μm, about 3.0 μm, about 3.5 μm, about 4.0 μm, about 4.5 μm, about 5.0 μm, about 5.5 μm, about 6.0 μm, about 6.5 μm, or about 7.0 μm, or within a range consisting of any two of these values.

[0044] In some embodiments, the second polymer comprises a homopolymer formed from any one of the monomers ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene, or the second polymer comprises a copolymer formed from at least two monomers selected from the group consisting of ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene.

[0045] In some embodiments, the second polymer is a copolymer of styrene, acrylonitrile, isobutyl acrylate, and / or ethyl methacrylate. In some embodiments, the second polymer is 80% styrene, 5% butadiene, 5% isobutyl acrylate, and 10% acrylonitrile. In some embodiments, the second polymer is 80% styrene, 10% isobutyl acrylate, and 10% acrylonitrile. In some embodiments, the second polymer is 80% styrene, 10% ethyl methacrylate, and 10% acrylonitrile.

[0046] In some embodiments, the second coating layer further comprises a second auxiliary binder. The mass ratio of the second polymer to the second auxiliary binder is 2 to 20. In some embodiments, the mass ratio of the second polymer to the second auxiliary binder is 2, 4, 6, 8, 10, 14, or 16, or within a range consisting of any two of these values. Without being limited to any theory, if the mass ratio of the second polymer to the second auxiliary binder is too low (e.g., less than 2), the content of the second polymer decreases, which affects the adhesive strength between the second coating layer and the electrode piece. If the mass ratio of the second polymer to the second auxiliary binder is too high (e.g., more than 20), the internal cohesion of the second coating layer decreases, and the adhesive performance of the second coating layer decreases. By controlling the mass ratio of the second polymer to the second auxiliary binder within the above range, it is possible to provide excellent adhesive strength between the second coating layer and the electrode piece.

[0047] In some embodiments, the mass percentage of the second polymer is 75% to 92.5% and the mass percentage of the second auxiliary binder is 7.5% to 25% relative to the total mass of the second coating layer. By controlling the contents of the second polymer and the second auxiliary binder within the above ranges, a second coating layer having excellent adhesion performance can be obtained, and high adhesion can be provided between the second coating layer and the negative electrode, thereby improving the performance of the lithium ion battery at low temperatures.

[0048] The second auxiliary binder is not particularly limited as long as it satisfies the requirements of the present invention. For example, the second auxiliary binder can include at least one of polymethacrylate, sodium carboxymethylcellulose, and dimethylsiloxane.

[0049] In some embodiments, the second coating layer further comprises a second wetting agent. The second wetting agent is not particularly limited and may be any agent that satisfies the requirements of the present invention, for example, organosiloxane. The mass percentage of the second wetting agent is 0.1% to 1% relative to the total mass of the second coating layer.

[0050] In some embodiments, the coating surface density W2 of the second coating layer is 0.1 g / m 2 ~1g / m 2 In some embodiments, the second coating layer has a coating areal density W2 of about 0.2 g / m 2 , about 0.3g / m 2 , about 0.4 g / m 2 , about 0.5g / m 2 , about 0.6g / m 2 , about 0.7g / m 2 , about 0.8g / m 2 , or about 0.9 g / m 2 or in a range consisting of any two of these values.

[0051] The applicant has discovered that the strength and heat resistance of the separator can be further improved by adding inorganic particles to the separator.

[0052] In some embodiments, the first coating layer and / or the second coating layer includes inorganic particles, which in the first coating layer or the second coating layer account for 40% to 90% of the total weight of the coating layer.

[0053] In some embodiments, the separator further includes a heat-resistant layer. The heat-resistant layer may be provided between the substrate and the first coating layer, or between the substrate and the second coating layer. The heat-resistant layer includes inorganic particles. By providing the heat-resistant layer between the substrate and the first coating layer, the strength and heat resistance of the separator can be further improved. The thickness of the heat-resistant layer is not particularly limited as long as it satisfies the requirements of the present invention, and may be, for example, 0.6 μm to 40 μm.

[0054] In another embodiment, the heat-resistant layer includes inorganic particles, a binder, a dispersant, and a wetting agent in a mass ratio of (87-98.5):(1-10):(0.5-2):(0-1). The binder and the wetting agent are defined as the first auxiliary binder and the first wetting agent in the first coating layer. The dispersant is not particularly limited as long as it satisfies the requirements of the present invention. For example, the dispersant may be polyacrylic acid.

[0055] The inorganic particles in the heat-resistant layer, the first coating layer, and the second coating layer are not particularly limited as long as they can achieve the object of the present invention. The inorganic particles include at least one of boehmite, magnesium hydroxide, alumina, titania, silica, zirconia, tin dioxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride, and aluminum nitride.

[0056] In some embodiments, the inorganic particles have a particle size Dv50 of 0.5 μm to 35 μm. It is not desirable for the inorganic particles to have a particle size that is too large or too small. If the particle size of the inorganic particles is too large (e.g., larger than 35 μm), it is difficult to realize a thin coating design, which affects the energy density of the lithium ion battery. If the particle size of the inorganic particles is too small (e.g., smaller than 0.5 μm), the pores where the inorganic particles are deposited are reduced, which affects the transport of ions and affects the dynamic properties of the lithium ion battery. By controlling the Dv50 of the inorganic particles within the above range, the separator can have high energy density and excellent dynamic properties.

[0057] In some embodiments, the adhesive strength between the first coating layer and the positive electrode is 4 N / m to 20 N / m. In some embodiments, the adhesive strength between the first coating layer and the positive electrode is about 5 N / m, about 6 N / m, about 7 N / m, about 8 N / m, about 9 N / m, about 10 N / m, about 11 N / m, about 12 N / m, about 13 N / m, about 14 N / m, about 15 N / m, about 16 N / m, about 17 N / m, about 18 N / m, or about 19 N / m, or within a range consisting of any two of these values.

[0058] In some embodiments, the adhesive strength between the second coating layer and the negative electrode is 5 N / m to 20 N / m. In some embodiments, the adhesive strength between the second coating layer and the negative electrode is about 6 N / m, about 7 N / m, about 8 N / m, about 9 N / m, about 10 N / m, about 11 N / m, about 12 N / m, about 13 N / m, about 14 N / m, about 15 N / m, about 16 N / m, about 17 N / m, about 18 N / m, or about 19 N / m, or within a range consisting of any two of these values.

[0059] In some embodiments, the adhesive strength between the first coating layer and the negative electrode is 3 N / m to 15 N / m. In some embodiments, the adhesive strength between the first coating layer and the negative electrode is about 4 N / m, about 5 N / m, about 6 N / m, about 7 N / m, about 8 N / m, about 9 N / m, about 10 N / m, about 11 N / m, about 12 N / m, about 13 N / m, or about 14 N / m, or within a range consisting of any two of these values.

[0060] In some embodiments, the adhesive strength between the second coating layer and the positive electrode is 5 N / m to 20 N / m. In some embodiments, the adhesive strength between the second coating layer and the positive electrode is about 6 N / m, about 7 N / m, about 8 N / m, about 9 N / m, about 10 N / m, about 11 N / m, about 12 N / m, about 13 N / m, about 14 N / m, about 15 N / m, about 16 N / m, about 17 N / m, about 18 N / m, or about 19 N / m, or within a range consisting of any two of these values.

[0061] In some embodiments, when the number of wound layers of the positive electrode and the negative electrode is N, N satisfies N≧4. In some embodiments, N satisfies 6≦N≦35. In some embodiments, N satisfies 8≦N≦30. In some embodiments, N satisfies 10≦N≦25. In some embodiments, N is about 5, about 10, about 15, about 20, about 25, about 30, or about 35, or within a range consisting of any two of these values.

[0062] In some embodiments, the first coating layer is provided on the curved portion.

[0063] Second, the method for preparing the secondary battery: Hereinafter, the method for preparing a secondary battery of the present invention will be described in detail, taking a lithium ion battery as an example.

[0064] Separator: The separator includes a substrate, a first coating layer provided on a first surface of the substrate, and a second coating layer provided on a second surface opposite to the first surface. The substrate is a nonwoven fabric, a membrane, or a composite membrane having a porous structure, and the material of the substrate is at least one selected from polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be selected and used. The first coating layer and the second coating layer are, respectively, any of the first coating layer and the second coating layer described in the above examples.

[0065] Preparation of separator: (1) Preparation of inorganic coating layer: Inorganic particles, binder, dispersant, and wetting agent are dispersed in a solvent, thoroughly stirred to make uniform, and then applied to one or two surfaces of a separator substrate and dried to obtain a separator having an inorganic coating layer located on one or two surfaces of the substrate (abbreviated as "inorganic coating layer separator" or "heat-resistant layer").

[0066] (2) Preparation of the first coating layer: The selected first polymer, the first wetting agent, and the first auxiliary binder are dispersed in a solvent system, and in some embodiments, inorganic particles can also be added, and after sufficient stirring and uniform mixing, the mixture is applied onto the first surface of the separator substrate or onto any surface of the inorganic coating layer separator of step (1), and dried to obtain a separator having a first coating layer located on the first surface of the substrate, or a separator having a first coating layer located on any surface of the inorganic coating layer separator of step (1).

[0067] (3) Preparation of the second coating layer: The selected second polymer, the second wetting agent, and the second auxiliary binder are dispersed in a solvent system, and in some embodiments, inorganic particles can be further added, and then the mixture is thoroughly stirred and mixed uniformly, and then coated on the second surface of the separator obtained in step (2), and dried to obtain a final separator, which has a first coating layer located on the first surface of the substrate and a second coating layer located on the second surface of the substrate, or an inorganic coating layer located on the first surface of the substrate, a first coating layer located on the inorganic coating layer, an inorganic coating layer located on the second surface of the substrate, and a second coating layer located on the inorganic coating layer, or an inorganic coating layer located on the first surface of the substrate, a first coating layer located on the inorganic coating layer, and a second coating layer located on the second surface of the substrate, or a first coating layer located on the first surface of the substrate, an inorganic coating layer located on the second surface of the substrate, and a second coating layer located on the inorganic coating layer.

[0068] Preparation of the negative electrode: The negative electrode active material, binder, dispersant and conductive material are dispersed in a solvent system at a certain mass ratio, thoroughly stirred and mixed uniformly, and then coated on the negative electrode current collector, dried and cold rolled to obtain the negative electrode.

[0069] In some examples, the binder includes, but is not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyfluoroethylene, polymers containing ethyleneoxy groups, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, poly(1,1-difluoroethylene), polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, or nylon.

[0070] In some embodiments, the negative electrode active material includes a conductive material, which may include, but is not limited to, natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, metal fiber, copper, nickel, aluminum, silver, or a polyphenylene derivative.

[0071] In some examples, the negative electrode current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a polymer substrate coated with a conductive metal.

[0072] In some examples, the solvent can include, but is not limited to, N-methylpyrrolidone.

[0073] Preparation of positive electrode: The positive electrode material, binder, dispersant and conductive material are dispersed in a solvent system at a certain mass ratio, thoroughly stirred and mixed uniformly, and then coated on a positive electrode current collector, dried and cold rolled to obtain a positive electrode.

[0074] In some embodiments of the present invention, the positive electrode current collector may be, but is not limited to, an aluminum foil or a nickel foil.

[0075] In some embodiments, the positive electrode material includes a material capable of absorbing and releasing lithium (Li) (hereinafter, may be referred to as a "positive electrode material capable of absorbing / releasing lithium Li"). Examples of positive electrode materials capable of absorbing / releasing lithium (Li) include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxygen phosphate, lithium iron phosphate, lithium titanate, and lithium-containing manganese-based materials.

[0076] In the above positive electrode material, the chemical formula of lithium cobalt oxide is Li x Co a M1 b O 2-c where M1 is selected from the group consisting of nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La), zirconium (Zr), silicon (Si), and combinations thereof, and the values ​​of x, a, b, and c are within the ranges of 0.8≦x≦1.2, 0.8≦a≦1, 0≦b≦0.2, and −0.1≦c≦0.2, respectively.

[0077] In the above positive electrode material, the chemical formula of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide is Li y Ni d M2 e O 2-fwherein M2 is selected from the group consisting of cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), zirconium (Zr), silicon (Si), and combinations thereof, and the values ​​of y, d, e, and f are within the ranges of 0.8≦y≦1.2, 0.3≦d≦0.98, 0.02≦e≦0.7, and −0.1≦f≦0.2, respectively.

[0078] In the above positive electrode material, the chemical formula of lithium manganese oxide is Li z Mn 2-g M3 g O 4-h where M3 is selected from the group consisting of cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), and combinations thereof, and the values ​​of z, g, and h are within the ranges of 0.8≦z≦1.2, 0≦g≦1.0, and −0.2≦h≦0.2, respectively.

[0079] In some embodiments, the conductive material improves the conductivity of the active material by providing a conductive path to the active material. The conductive material may include at least one of acetylene black, ketjen black, natural graphite, carbon black, carbon fiber, metal powder, and metal fiber (e.g., copper, nickel, aluminum, or silver), but examples of the conductive material are not limited thereto. In some embodiments, the amount of the conductive material may be appropriately adjusted. The amount of the conductive material ranges from 1 part by weight to 30 parts by weight with respect to 100 parts by weight in total of the positive electrode active material, the conductive material, and the binder.

[0080] In some embodiments, examples of the solvent include, but are not limited to, N-methylpyrrolidone, acetone, or water. In some embodiments, the amount of the solvent can be appropriately adjusted.

[0081] In some embodiments, the binder can aid in adhesion between the active material and the conductive material, or between the active material and the current collector. Examples of the binder include, but are not limited to, polyvinylidene fluoride, polyvinylidene chloride, carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polypropylene, polyethylene, and various polymers. The amount of the binder ranges from 1 part by weight to 30 parts by weight based on 100 parts by weight of the total of the active material, conductive material, and binder.

[0082] In some embodiments, the current collector has a thickness in the range of 3 μm to 20 μm, but the invention is not limited thereto. The current collector is conductive and does not cause adverse chemical changes in the fabricated battery. Examples of the current collector include, but are not limited to, copper, stainless steel, aluminum, nickel, titanium, or alloys (e.g., copper-nickel alloys). In some embodiments, the surface of the current collector may include fine irregularities to enhance adhesion between the surface of the current collector and the active material. In some embodiments, the current collector can be used in various forms, examples of which include, but are not limited to, a film, sheet, foil, mesh, porous structure, foam, or non-woven fabric.

[0083] Electrolyte: In some embodiments, the electrolyte includes an organic solvent, a lithium salt, and an additive. In some embodiments, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, and ethyl propionate.

[0084] In some embodiments, the lithium salt comprises at least one of an organic lithium salt and an inorganic lithium salt, and in some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalato)borate LiB(C2O4)2 (LiBOB), and lithium difluoro(oxalato)borate LiBF2(C2O4) (LiDFOB).

[0085] In some embodiments, the content of the lithium salt is 5% to 30% by weight of the electrolyte. In some embodiments, the content of the lithium salt is 6% to 25% by weight of the electrolyte. In some embodiments, the content of the lithium salt is 8% to 20% by weight of the electrolyte. In some embodiments, the content of the lithium salt is 6% to 18% by weight of the electrolyte.

[0086] In some embodiments, the additive comprises at least one of fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, vinyl sulfate, adiponitrile, succinonitrile, glutaronitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, succinic anhydride, lithium difluorophosphate, and lithium tetrafluoroborate.

[0087] Battery preparation: The positive electrode, separator, and negative electrode are stacked in order, the separator is placed between the positive electrode and the negative electrode to play the role of isolation, and N layers are wound to obtain a bare cell. The wound bare cell is placed in an outer casing, electrolyte is injected and packaged, and a complete cell is obtained through processes such as formation, degassing, and trimming. Here, the number of winding layers is defined as follows: Taking the curved part on either side (or the flat part on either side) as the basis, each time a layer of a positive electrode, a separator, and a negative electrode appears, it is represented as one layer, and the sum of all the overlapping layers is the number of winding layers of the battery.

[0088] 3. Electrochemical equipment: The present invention further provides an electrochemical device including the secondary battery described above. In some embodiments, the secondary battery is a lithium secondary battery, such as a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0089] 4. Electronic equipment: The present invention provides an electronic device including the secondary battery described above.

[0090] According to some embodiments of the present invention, the electronic device may include, but is not limited to, a laptop computer, a pen-based computer, a mobile computer, an e-book player, a mobile phone, a portable facsimile machine, a portable copier, a portable printer, a stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a walkie-talkie, an electronic organizer, a calculator, a memory card, a portable tape recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, an electric power assisted bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, a power tool, a strobe, a camera, a large household battery, and the like.

[0091] Five, specific examples: The present invention will be described in more detail below with reference to examples. However, it should be understood that the following examples are merely illustrative and do not limit the embodiments of the present invention.

[0092] (Examples 1 to 45 and Comparative Examples 1 to 3) Example 1: Separator: (1): Based on a mass ratio of 93.1%:5.0%:1.5%:0.4%, boehmite, polymethyl methacrylate, polyacrylic acid, and polyoxyethylene ether were dispersed in a solvent system (water), thoroughly stirred to make uniform, and then applied to the first surface of a separator substrate and dried to obtain a separator having an inorganic coating layer located on the first surface of the base film of the substrate (abbreviated as "inorganic coating layer separator" or "heat-resistant layer"). Here, it should be understood that although inorganic particles are applied to the first surface of the base film of the substrate, inorganic particles may be applied to the other surface of the base film of the substrate, or may be applied simultaneously to both surfaces of the base film of the substrate, or inorganic particles may not be applied on both surfaces of the base film of the substrate.

[0093] (2) The selected first polymer (polyvinylidene fluoride, 100%), first auxiliary binder (polyacrylonitrile) and first wetting agent (polyoxyethylene ether) were dispersed in water in mass ratios of 89.5%, 10%, and 0.5%, and thoroughly stirred to uniformly mix, and then applied to the first surface of the inorganic coating layer separator obtained in step (1) (i.e., the first polymer was applied onto the inorganic coating layer), followed by drying to obtain a separator having a first coating layer located on the first surface of the inorganic coating layer separator.

[0094] (3) The selected second polymer (a copolymer formed by polymerizing 80% styrene, 10% isobutyl acrylate, and 10% acrylonitrile), the second auxiliary binder (polymethacrylate), and the second wetting agent (organosiloxane) were dispersed in water at mass ratios of 79.5%, 20%, and 0.5%, and thoroughly stirred to mix uniformly. The mixture was then applied to the second surface of the inorganic coating layer separator obtained in step (2), and dried to obtain the separator required in this embodiment.

[0095] Here, in the manufacturing process of the separator, the coverage of the first coating layer (i.e., the ratio of the orthogonal projection area of ​​the first coating layer on the first surface to the area of ​​the first surface) is 40%, the softening point of the first polymer is 125°C, the Dv50 of the first polymer is 12 µm, and the areal density W1 of the first polymer is 1 g / m 2 and the number of particles of the first polymer having a length of 10 μm to 30 μm in an area of ​​250 μm × 200 μm on the surface of the first coating layer is 25. Here, the Dv50 of the second polymer is 0.7 μm, and the surface density W2 of the second polymer is 0.2 g / m 2 It is.

[0096] Positive electrode: Lithium cobalt oxide as the positive electrode active material, acetylene black as the conductive agent, and polyvinylidene fluoride (PVDF) as the binder were thoroughly mixed in an N-methylpyrrolidone solvent system in a weight ratio of 97:2:1 to obtain a homogeneous mixture. The mixture was then applied to an Al foil as a positive electrode current collector, dried, and cold-rolled to obtain a positive electrode.

[0097] Negative electrode: Artificial graphite as an active material, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as a binder, and sodium carbomethylcellulose (CMC) as a thickener were thoroughly mixed in a deionized water solvent system in a mass ratio of approximately 95:2:2:1, and then the mixture was applied to a Cu foil, dried, and cold-rolled to obtain a negative electrode.

[0098] Electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (abbreviated as EC), diethyl carbonate (abbreviated as DEC), and propylene carbonate (abbreviated as PC) were mixed uniformly in a weight ratio of 2:6:2, and then the lithium salt LiPF6, which had been thoroughly dried, was dissolved in the above solvent, where the content of LiPF6 was 1 mol / L, and then 1.5% 1,3-propane sultone, 3% fluoroethylene carbonate, and 2% adiponitrile were added. Here, the content of each substance was based on the total weight of the electrolyte.

[0099] Preparation of the battery: The positive electrode, separator, and negative electrode are stacked in order, the separator is placed between the positive electrode and the negative electrode to play the role of isolation, wound, put into the outer casing, the mixed electrolyte is injected and sealed, and the battery is obtained through the processes of formation, hot pressing, degassing, trimming, etc. Here, the number of winding layers is 20. When the distance between the adjacent negative electrode and the positive electrode in the curved part of the winding structure is d1, and the distance between the adjacent negative electrode and the positive electrode in the flat part of the winding structure is d2, d1 / d2 is 2, where d1 and d2 adopt the same unit. Here, d1 / d2 can be realized, for example, by coating technology or hot pressing technology. When the weight of the coating is large, d1 is large. After the battery is hot pressed, d1 remains almost unchanged, and d2 is greatly reduced. Different weights of coating and hot pressing conditions can be obtained to obtain different d1 and d2, thereby controlling the magnitude of d1 / d2. The magnitude of d1 / d2 can also be controlled by non-uniform coating. For example, the first coating layer is disposed so as to be located primarily on the curved portion.

[0100] Table 1 below specifically shows the differences in battery parameters between Examples 1 to 45 and Comparative Examples 1 to 3. Comparative Example 3 does not have a coating layer, and therefore does not have the first / second auxiliary binder and the first / second wetting agent. The types and contents of the first / second auxiliary binder and the first / second wetting agent in the other Examples and Comparative Examples are the same as the parameters in Example 1 above, and are not further described in the table. The following table only shows the different parameter settings of each Example and Comparative Example. Example 45 differs from Example 4 only in that Example 43 does not include an inorganic coating layer.

[0101] [Table 1] JPEG2025511106000003.jpg187170JPEG2025511106000004.jpg224170JPEG2025511106000005.jpg224170JPEG2025511106000006.jpg224170 JPEG2025511106000007.jpg224170JPEG2025511106000008.jpg187170JPEG2025511106000009.jpg224170JPEG2025511106000010.jpg147170

[0102] As can be seen from Table 1 above, the differences between Examples 1 to 45 and Comparative Examples 1 to 3 are d1 / d2, the number of winding layers, the number of particles of the first polymer having a maximum length of 10 μm to 30 μm in a 250 μm × 200 μm area on the surface of the first coating layer, the coverage of the first coating layer, the type and content of the first polymer, the softening point of the first polymer, Dv50 of the first polymer, areal density of the first polymer, the type and content of the second polymer, Dv50 of the second polymer, areal density of the second polymer, and the presence or absence of a coating layer.

[0103] Other than the above differences, there are no differences between Examples 1 to 45 and Comparative Examples 1 to 3 in the negative electrode, electrolyte, separator, and the like.

[0104] Measurement method: (1) Measurement method for d1 and d2 Using an electronic computed tomography (CT) scanner, the curved and flat parts of the battery were scanned at a rate of 300% to obtain cross-sectional images. The shortest distance between two adjacent layers of positive current collectors in the curved part was measured at 10 points, and the average value was D1 ("adjacent" here does not mean that they are in physical contact with each other, but that there is no other positive current collector between the two measured positive current collectors; obviously, there is also a separator and a negative current collector between the two positive current collectors). d1=D1 / 2. The shortest distance between the two adjacent layers of positive current collectors in the flat part was measured at 10 points, and the average value was D2. d2=D2 / 2. The adjacent two layers of positive current collectors selected from the curved part and the adjacent two layers of positive current collectors selected from the flat part were connected to each other and corresponded to each other, that is, the two layers of positive current collectors for measuring the curved part and the two layers of positive current collectors for measuring the flat part were the same two layers of positive current collectors, as shown in FIG. 1.

[0105] Specifically, FIG. 1 was referred to. 1 is a positive electrode film piece (positive electrode active material layer), 2 is a positive electrode current collector, 3 is a separator, 4 is a negative electrode film piece (negative electrode active material layer), and 5 is a negative electrode current collector. The positive electrode current collector 2 has a positive electrode film piece (positive electrode active material layer) 3 on both the upper and lower surfaces, and the negative electrode current collector 5 has a negative electrode film piece (negative electrode active material layer) 4 on both the upper and lower surfaces. Ten points were taken to measure the distance between two adjacent layers of positive electrode current collectors in the curved part, and the average value was taken as D1. Ten points were taken to measure the distance between two adjacent layers of positive electrode current collectors in the flat part, and the average value was taken as D2. d1=D1 / 2 and d2=D2 / 2 were calculated.

[0106] (2) Number of particles of the first polymer

[0107] The separator coated with the first coating layer was cut into samples of 10 mm x 10 mm, and then the samples were placed in an SEM and observed at a magnification of 500x. Five randomly selected areas of 250 μm x 200 μm were observed within the field of view, and the number of particles of the first polymer whose maximum length was between 10 μm and 30 μm in the selected areas was recorded, and the average value, i.e., the number of particles of the first polymer whose maximum length was between 10 μm and 30 μm in a unit area of ​​the first coating layer, was taken.

[0108] (3) Coverage of the first coating layer

[0109] The separator coated with the first coating layer was cut into a 10mm x 10mm sample, and then the sample was placed in an SEM and observed at a magnification of 500x, and five 250μm x 200μm areas were selected randomly within the field of view. The first coating layer was labeled and fitted using an image segmentation algorithm to obtain its coverage area S, and the coverage rate was calculated by taking the average coverage rate of the five positions, as follows: coverage rate = S / (250 x 200) * 100%, and the coverage rate of the first coating layer was obtained by taking the average coverage rate of the five positions.

[0110] (4) Softening point

[0111] General-purpose differential scanning calorimeter (DSC) method: 5 mg of each sample of the first polymer prepared in each Example and Comparative Example was taken, heated to 150°C at a heating rate of 5°C / min, and a DSC curve was taken. The softening point, i.e., softening temperature, of the first polymer was determined from the obtained DSC curve.

[0112] (5) Particle Dv50

[0113] The first polymer was dispersed in deionized water and stirred uniformly. The slurry was collected and the particle size was measured by a Maruban particle sizer, i.e., the dispersed sample was added to the Maruban particle sizer and the measurement was started. After the measurement was completed, the particle size data of the first polymer could be obtained. The Dv50 of the inorganic particles and the second polymer were measured using the same method.

[0114] (6) Areal density

[0115] The surface density of the coating layer was measured using an electronic balance with a precision of 0.0001 g. The separator substrate before coating was sampled and measured at 10,000 mm 2 The separator coated with the first coating layer was cut into 5 pieces of 10,000 mm 2 The average value M was weighed to obtain the weight of the separator coated with the first coating layer. The surface density of the first coating layer = Mm, and the unit was converted to g / m 2 The areal density of the second coating layer was measured using the same method.

[0116] (7) Adhesive strength

[0117] The dry press adhesion of the separator and the positive and negative electrodes was measured using the 180° peel test standard. The separator and the positive and negative electrodes were cut into samples of 54.2mm x 72.5mm, the separator was combined with the positive and negative electrodes, hot pressed using a hot press machine, and maintained under conditions of a temperature of 85°C and a pressure of 1Mpa for 85 seconds. The combined sample was cut into a 15mm x 54.2mm slit, and the adhesion was measured according to the 180° peel test standard. The adhesion between the first coating layer and the negative electrode, the adhesion between the first coating layer and the negative electrode, the adhesion between the second coating layer and the positive electrode, and the adhesion between the second coating layer and the negative electrode were measured, respectively.

[0118] (7) Battery width

[0119] The width of the cell was measured using a projection projector, and the wound cell was placed between two transparent glass plates, the length of the cell was parallel to the width of the glass plates, the length of the glass plates was at least 100% larger than the width of the cell, and the width of the glass plates was at least 10% larger than the length of the cell. The cell was clamped with two 30 kg jigs at the positions where the glass plates did not cover the cell in the length direction, and the cell was placed flat on the measurement table of the projection projector, and the width of the cell was measured using the projection projector, and the width of the cell was measured at five positions along the length direction and the average value was taken to obtain the width of the cell.

[0120] (8) Battery hardness

[0121] The hardness of the battery was measured by the three-point bending method. The operation was performed at 25°C, the battery was fully discharged to 3.0V, and the tab was insulated. The interval of the lower support rod of the hardness test jig of the universal testing machine (Instron-3365) was adjusted to 2 / 3 of the width of the battery, and the battery was placed flat on the lower jig, with the width direction perpendicular to the support rod. The upper pressing head of the jig was adjusted to be perpendicular to the width direction and located at the center position of the battery, and pressed down at a speed of 5mm / min. When the upper pressing head began to touch the battery, the deformation displacement of the battery was recorded, and the measurement was stopped at the point when the load force decreased from maximum, and the maximum force resisting the deformation was taken as the maximum hardness of the battery. The lower support rod was circular and had a diameter of 10mm; the upper pressing head was circular and had a diameter of 10mm.

[0122] (9) Measurement method for battery rate discharge characteristics

[0123] Discharge characteristics at 0.5C under -20°C conditions: The battery was left in a 25°C environment for 5 minutes, charged at a constant current of 1.5C until the battery voltage reached 4.45V, charged at a constant voltage of 4.45V until the charge current reached 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.5C until the battery voltage reached 3V, and the discharge capacity of the first cycle was recorded as C1. The above charging process was repeated to fully charge the battery. Then, the battery was placed in a -20°C environment, left to stand for 60 minutes, and discharged at a constant current of 0.5C until the battery voltage reached 3V, and the discharge capacity was recorded as C2. The discharge characteristics at 0.5C at -20°C = C2 / C1*100%.

[0124] Discharge characteristics at different rates under 25℃ conditions: The battery was left at room temperature for 5 minutes, then charged at a constant current of 1.5C until the battery voltage reached 4.45V, then charged at a constant voltage of 4.45V until the charge current reached 0.05C, and then left to stand for 5 minutes, after which it was discharged at a constant current of 0.2C until the battery voltage reached 3V, and the discharge capacity of the first cycle was recorded as D1. The above charging process was repeated to fully charge the battery, and then it was discharged at a constant current of xC until the battery voltage reached 3V, and the discharge capacity at this time was recorded as Dx, and the discharge characteristics at different rates were = Dx / D1*100%, where x=2,5.

[0125] Capacity retention rate after 500 cycles under 12°C conditions: The battery to be measured was left standing at a measurement temperature of 12°C for 30 minutes, and the battery was charged at a constant current of 2C to 4.45V, and then charged at a constant voltage of 4.45V to 0.05C. After leaving it standing for 5 minutes, it was discharged at a constant current of 1C to 3.0V, and left standing for 5 minutes. The above charge / discharge process was repeated 500 times, and the discharge capacity after each cycle was recorded. The capacity retention rate of the battery after 500 cycles was calculated by the formula: Capacity retention rate after 500 cycles = (Discharge capacity after 500 cycles / Discharge capacity of the first cycle) x 100%.

[0126] Table 2 below shows the performances of Examples 1 to 45 and Comparative Examples 1 to 3.

[0127] [Table 2] JPEG2025511106000012.jpg205170JPEG2025511106000013.jpg214170JPEG2025511106000014.jpg214170JPEG2025511106000015.jpg56170

[0128] Examination of Results: 1. Examination of the presence or absence of the inorganic coating layer (i.e., heat-resistant layer), the first coating layer, and the second coating layer, and the influence of d1 / d2 on battery performance:

[0129] As can be seen from Table 1 above, Examples 1 to 45 satisfy 1 < d1 / d2 < 10. Here, the first surface of the separator in Examples 1 to 44 has a heat-resistant layer and a first coating layer located on the heat-resistant layer, and the second surface of the separator has a heat-resistant layer and a second coating layer located on the heat-resistant layer. The first surface and the second surface of the separator in Example 45 each have a first coating layer and a second coating layer. The difference between Comparative Example 1 and Examples 1 to 44 is that d1 / d2 = 1, the difference between Comparative Example 2 and Examples 1 to 44 is that d1 / d2 = 11, and the difference between Comparative Example 3 and Examples 1 to 45 is that the separator has no coating layer at all.

[0130] As can be seen from Table 2 above, the hardness of the batteries in Examples 1 to 45 and Comparative Examples 1 and 2 is equivalent (the specification requirement is greater than 120 N), but the discharge characteristics and low-temperature cycle characteristics of the batteries in Examples 1 to 45 are all superior to those of the batteries in Comparative Example 1 and Comparative Example 2. This is mainly because in Comparative Example 1, d1 / d2 is too low, the gap at the curved part of the battery is too small, and when the negative electrode expands during cycling, the electrolyte is compressed and discharged, resulting in local deficiency of the electrolyte, deterioration of the cycle characteristics. In Comparative Example 2, d1 / d2 is too large, the gap at the curved part of the battery is too large, and after the electrolyte is consumed, the electrolyte is likely to cause local deficiency, resulting in deterioration of the cycle characteristics.

[0131] The discharge characteristics and low-temperature characteristics of the batteries of Examples 1 to 45 and Comparative Example 3 are equivalent. However, the hardness of the batteries of Examples 1 to 45 is significantly greater than that of the batteries of Comparative Example 3. If the hardness of the batteries of Comparative Example 3 is too low, the batteries are likely to be deformed during assembly, and the winding structure is likely to be displaced, causing safety risks. Also, when the hardness is low, during the charge and discharge process of the battery, due to the disorderly expansion of the negative electrode, the interface between the positive electrode and the negative electrode is not flat, and local lithium precipitation occurs, affecting the battery characteristics.

[0132] Obviously, a separator is provided between the positive electrode and the negative electrode. The separator includes a base material, a first coating layer and a second coating layer respectively located on two opposing surfaces of the base material. The first coating layer includes a first polymer. And the distance d1 between the adjacent negative electrode and positive electrode at the curved part of the battery and the distance d2 between the adjacent negative electrode and positive electrode at the flat part of the battery satisfy 1 < d1 / d2 < 10, thereby providing a space for relaxing the expansion of the negative electrode during cycling, thereby avoiding local loss of the electrolytic solution due to the electrolytic solution being compressed and discharged. It is possible to avoid the gap being too large and there not being enough electrolytic solution to fill the gap, resulting in local loss of the electrolytic solution, and it is possible to ensure that the thickness of the main body part (i.e., the flat part) of the battery does not increase significantly. Furthermore, the hardness of the battery can be guaranteed and the adhesion between the separator and the positive and negative electrodes can be improved, thereby enhancing the rate characteristics and cycle characteristics of the battery and reducing losses such as the loss of the volume energy density of the battery.

[0133] As can be seen from further research of the present invention, compared with Example 45 without a heat-resistant coating layer, each characteristic of Example 4, especially the electrochemical characteristics, is further improved. This is mainly because the interface between the surface of the base material and the polymer coating layer is relatively dense and is disadvantageous for the transport of lithium ions. However, the inorganic particles in the heat-resistant coating layer can loosen this interface structure. For example, the inorganic particles can introduce some voids, making the transport of lithium ions smoother and reducing the diffusion resistance, etc., thereby further improving the electrical characteristics of the electrochemical device.

[0134] 2. Consideration of the number of winding layers: With reference to Tables 1 and 2, it can be seen that in some embodiments of the present invention, particularly in Examples 11 to 13, the number of winding layers of the battery is N, where N≧4. An increase in the number of winding layers leads to an increase in the pressure on the inner layer of the curved part of the battery. The greater the number of winding layers, the greater the pressure on the inner layer of the curved part of the battery, and the more likely it is that localized loss of electrolyte will occur. By using this separator, it is possible to provide a space for transporting and storing electrolyte in the curved part, and good electrical properties can be obtained for batteries with different numbers of winding layers.

[0135] 3. Consideration of the number of particles of the first polymer: Referring to Tables 1 and 2, it can be seen that in some embodiments of the present invention, especially in Examples 4 and 14-17, the number of the first polymer particles with a length of 10-30 μm in an area of ​​250 μm×200 μm on the surface of the first coating layer is 10-30. As can be seen from the present study, by controlling the number of the first polymer particles within this range, a better battery curve thickness can be obtained, and the higher the number, the larger the corresponding d1.

[0136] 4. Study of the coverage of the first polymer: Referring to Tables 1 and 2, it can be seen that in some embodiments of the present invention, particularly in Examples 4 and 18-22, the ratio of the orthogonal projection area of ​​the first coating layer on the first surface to the area of ​​the first surface is 5%-60%. As can be seen from the research of the present invention, if the coverage of the first coating layer is too low, the adhesion between the separator and the electrode piece will be too low, resulting in too low hardness of the battery; if the coverage of the first coating layer is too high, it is easy to cause blocking of the pores of the separator, affecting the transport of lithium ions, and ultimately affecting the electrical properties of the battery. By controlling the coverage of the first coating layer within the above range, good hardness of the battery can be obtained and good electrical properties can be maintained at the same time.

[0137] 5. First, consider the type of polymer: Referring to Tables 1 and 2, particularly in Examples 4 and 27 to 28, in some embodiments of the present invention, the first polymer includes a homopolymer formed from any one monomer selected from the group consisting of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride, or the first polymer includes a copolymer formed from at least two monomers selected from the group consisting of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride.

[0138] It should be understood that any of the homopolymers formed from any of the above monomers or copolymers formed from at least two of them can realize the technical solution of the present application and obtain ideal battery characteristics. However, as a result of further investigation, the following was found. On the other hand, when the first coating layer of the separator is formed using conventional aqueous polyvinylidene fluoride (PVDF) as the first polymer, its large particle size can secure space for the expansion of the negative electrode, but the softening point of the material is high, so the adhesion of the interface is low and the loss of the energy density of the battery is large (about 2% less than that of non-aqueous PVDF). In addition, the hardness of the battery is low, so it is easily deformed during assembly and the wound structure is easily misaligned, which causes safety risks. In addition, the hardness is low, so that during the charge and discharge process of the battery, the interface between the positive electrode and the negative electrode is not flat due to the disordered expansion of the negative electrode, which causes localized precipitation of lithium, which affects the battery characteristics. On the other hand, when non-aqueous PVDF is used as the first polymer to form the first coating layer of the separator, the gap at the interface is very small after hot pressing, which is easy to hinder the transport of electrolyte, and is easy to cause a shortage of electrolyte in both the curved and flat parts of the battery, which causes a shortage of lithium absorption and even causes lithium precipitation. However, if at least one of hexafluoropropylene, ethylene, propylene, vinyl chloride or propylene chloride is added to PVDF to form the first coating layer, it can provide an ideal space for the expansion of the negative electrode and ensure the adhesion between the separator and the positive and negative electrodes.

[0139] 6. Study on the softening point of the first polymer: With reference to Tables 1 and 2, it can be seen that in some embodiments of the present invention, particularly in Examples 4 and 25-28, the softening point of the first polymer is 90°C to 150°C. As can be seen from the research of the present invention, if the softening point of the first polymer is too low, it is easy to cause the phenomenon of blocking the separator pores, which affects the transportation of lithium ions and ultimately affects the electrical characteristics of the battery, while if the softening point of the first polymer is too high, the adhesive force between the separator and the electrode piece is reduced, which causes the active material to fall off during cycling, ultimately affecting the electrical characteristics of the battery. By controlling the softening point of the first polymer within the above range, ideal electrical characteristics can be obtained.

[0140] 7. Study of Dv50 of the first polymer: With reference to Tables 1 and 2, it can be seen that in some examples of the present invention, particularly in Examples 4 and 29-31, the Dv50 of the first polymer is 3 μm to 16 μm. As can be seen from the research of the present invention, the larger the Dv50 of the first polymer, the easier it is to create a desired gap (i.e., the d1) in the curved part of the battery, but if the Dv50 is too large, the volumetric energy density of the battery decreases. By controlling the Dv50 of the first polymer within the above range, it is possible to reduce the loss of volumetric energy density while ensuring space for the expansion of the negative electrode.

[0141] 8. Consideration of the coating area density of the first coating layer: Referring to Tables 1 and 2, particularly in Examples 4 and 32 to 34, in some embodiments of the present invention, the coating surface density W1 of the first coating layer is 0.4 g / m 2 ~2g / m 2 It can be seen from the research of the present invention that the smaller the coating surface density W1 of the first coating layer, the smaller the thickness of the curved part of the battery. By controlling the coating surface density W1 of the first coating layer within the above range, better electrical properties can be achieved.

[0142] 9. Consideration of the type of second polymer, Dv50 and coating area density of the second coating layer: With reference to Tables 1 and 2, in some embodiments of the present invention, particularly in Examples 4 and 35-36, the second polymer includes a homopolymer formed from any one of monomers selected from ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene, or the second polymer includes a copolymer formed from at least two monomers selected from the group consisting of ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene. Any second polymer within the above range can obtain strong adhesion between the separator and the negative electrode. With reference to Tables 1 and 2, in some embodiments, particularly in Examples 4 and 37-41, the Dv50 of the second polymer is 0.2 μm to 8 μm. Referring to Tables 1 and 2, particularly in Examples 4 and 42 to 44, in some examples, the coating surface density W2 of the second coating layer is 0.1 g / m 2 ~1g / m 2 It can be seen that.

[0143] The above are the embodiments enumerated in the present invention. However, since the applicant cannot enumerate all the embodiments, all other equivalent embodiments based on the teachings of the present invention are within the scope of protection of the present invention. As described above, the present invention provides a method for manufacturing a secondary battery having relatively high rate characteristics, cycle characteristics and hardness, which is simple, easy and suitable for industrial production.

[0144] Throughout the specification, references to "some embodiments," "some of the embodiments," "one embodiment," "another example," "an example," "embodiment," or "some of the examples" mean that at least one embodiment or example of the invention includes a particular feature, structure, material, or characteristic described in that embodiment or example. Thus, the appearances of, for example, "in some embodiments," "in an embodiment," "in one embodiment," "in another example," "in one example," "in a particular example," or "an example" in various places throughout the specification do not necessarily refer to the same embodiment or example of the invention. Furthermore, particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.

[0145] Although exemplary embodiments have been described and illustrated, those skilled in the art should understand that the above-described embodiments should not be construed as limiting the present invention, and that modifications, substitutions, and alterations can be made to the embodiments without departing from the technical spirit, principles, and scope of the present invention.

Claims

1. A secondary battery, The secondary battery includes a positive electrode, a negative electrode, and a separator provided between the positive electrode and the negative electrode, the positive electrode, the separator, and the negative electrode are sequentially stacked and wound to form a wound structure including a curved portion and a flat portion; The separator includes a substrate, the substrate has a first surface and a second surface opposite the first surface; a first coating layer disposed on the first surface, the first coating layer comprising a first polymer; a second coating layer on the second surface; A secondary battery, wherein 1 < d1 / d2 < 10 is satisfied, where d1 is the distance between adjacent negative electrodes and positive electrodes in the curved portion, and d2 is the distance between adjacent negative electrodes and positive electrodes in the flat portion.

2. 2. The secondary battery according to claim 1, wherein the number of particles of the first polymer having a maximum length of 10 μm to 30 μm in an area of ​​250 μm x 200 μm on the surface of the first coating layer is 10 to 30.

3. the first polymer comprises a homopolymer formed from any one of the monomers vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride; or The first polymer comprises a copolymer formed from at least two monomers selected from the group consisting of vinylidene fluoride, hexafluoropropylene, ethylene, propylene, vinyl chloride, and propylene chloride; The secondary battery according to claim 1 .

4. 2. The secondary battery according to claim 1, wherein the softening point of the first polymer is 90°C to 150°C.

5. 2. The secondary battery according to claim 1, wherein the first polymer has a Dv50 of 3 μm to 16 μm.

6. 2. The secondary battery according to claim 1, wherein a ratio of an orthogonal projected area of ​​said first coating layer on said first surface to an area of ​​said first surface is 5% to 60%.

7. The coating surface density W1 of the first coating layer is 0.4 g / m 2 ~2g / m 2 The secondary battery according to claim 1 ,

8. 2. The secondary battery according to claim 1, wherein the second coating layer comprises a second polymer, and the second polymer has a Dv50 of 0.2 μm to 8 μm.

9. The second polymer includes a homopolymer formed from any one of the monomers ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene; or 9. The secondary battery according to claim 8, wherein the second polymer comprises a copolymer formed from at least two monomers selected from the group consisting of ethyl acrylate, butyl acrylate, ethyl methacrylate, styrene, chlorostyrene, fluorostyrene, methylstyrene, acrylic acid, methacrylic acid, maleic acid, acrylonitrile, and butadiene.

10. The coating surface density W2 of the second coating layer is 0.1 g / m 2 ~1g / m 2 The secondary battery according to claim 1 ,

11. The adhesive strength between the first coating layer and the positive electrode is 4 N / m to 20 N / m; or The secondary battery according to claim 1 , wherein the adhesive strength between the second coating layer and the negative electrode is 5 N / m to 20 N / m.

12. The adhesive strength between the first coating layer and the negative electrode is 3 N / m to 15 N / m; and The secondary battery according to claim 1 , wherein the adhesive strength between the second coating layer and the positive electrode is 5 N / m to 20 N / m.

13. The secondary battery according to claim 1 , wherein N is the number of wound layers of the positive electrode and the negative electrode, and N satisfies N≧4.

14. The secondary battery according to claim 1 , wherein the first coating layer is provided on the curved portion.

15. An electrochemical device comprising the secondary battery according to any one of claims 1 to 14.

16. An electronic device comprising the secondary battery according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Battery element

    JP2014007165A